벼 무논직파 재배 안정성 확보를 위한 조건 및 재배적지 설정 - 황운하; Woon-ha Hwang; 정재혁; Jae-hyeok Jeong; 이현석; Hyen-seok Lee; 양서영; Seo-yeong Yang; 이충근; Chung-keun Lee; 임연화; Yeon-hwa Lim; et al. (Korean journal of crop science, 2019)
Wet direct-seeding (WDS) is an important method for improving the competitiveness of rice production in South Korea. We analyzed the optimum direct-seeding date to establish the rice standing rate in each area and selected suitable areas for WHS by considering the heading stage limit date for improving cultivation safety. As a result, the rice direct-seeding date to control weedy rice was around 5.15, 5.17-5.19, and after 5.20 in southern Youngnam, southern Honam, and the Middle Coast areas, respectively. However, the optimum seeding date for good standing rice was in late March in most areas. Analyzing by area, most of the southern plains and parts of the central inland plain are suitable for WHS. However, most parts of Gwangwon-do, and the northern parts of Chungbuk, Gyeongbuk, and Yeonghonam areas are not suitable for WHS, and should therefore avoid WHS.